Practice Makes Perfect: New Practitioners’ Perspectives on Trends in Legal Education - Claire Botnick; Cort VanOstran (Washington University Journal of Law & Policy, 2017)
This Essay, by attorneys Claire Botnick and Cort VanOstran, both recent graduates of Washington University School of Law, offers a perspective on the efficacy and shortcomings of recent modal changes in legal training. Botnick and VanOstran have a point of view situated between a student’s immediate exposure but limited perspective, and the established practitioner’s measured but distant analysis. Botnick and VanOstran emphasize the importance of academic programs that prioritize a student’s interaction with the law through curricular offerings, clinical experiences, and oral advocacy training.
Keywords: law school; legal education; legal training; law students; clinical experiences; oral advocacy